Morphological Traits and Water–Nutrient Utilization Efficiency of Hippophae rhamnoides Fine Roots Under Different Stubble Heights in Arsenic Sandstone Area, Inner Mongolia - Yajie Xu; Yuefeng Guo; Yongjie Yue; Longfei Hao; Wei Qi; Runhong Gao; Xiaoyu Dong (Plants)
Hippophae rhamnoides (family Elaeagnaceae) is a deciduous shrub that has become a uniquely advantageous species in the arsenic sandstone area of Inner Mongolia due to its well-developed root system and strong tillering ability. This study, by taking 10-year-old H. rhamnoides in the arsenic sandstone area as the research object and analyzing the morphological traits of their fine roots and their coordination within soil under different stubble heights (0, 10, 15, and 20 cm) and non-stubble treatment, aims to select the optimal stubble height that is most conducive to the rejuvenation of H. rhamnoides and thus improve the decline in the productivity of H. rhamnoides in this region. The results reveal significant differences in fine root and soil properties under different stubble heights (p < 0.05). Among different traits, fine root area density shows the highest total coefficient of variation, making it the most sensitive trait. Principal component analysis results indicate that after stubble treatment, the traits of H. rhamnoides fine roots center on high specific surface area (0.316) + high specific root length (0.312), shifting toward a resource-acquisition ecological strategy with the best foraging efficiency observed under a stubble height of 15 cm. Soil N:P and C:P can explain 66% and 61% of the root morphological traits strategies deployed during stubble treatment, respectively. Fine roots exhibit high adaptability to the breaking of phosphorus limitation and fixation of carbon and nitrogen.